The impact of intrauterine treatment on fetal tachycardia: a nationwide survey in Japan. (2nd October 2018) - Ueda, Keiko; Maeno, Yasuki; Miyoshi, Takekazu; Inamura, Noboru; Kawataki, Motoyoshi; Taketazu, Mio; Nii, Masaki; Hagiwara, Akiko; Horigome, Hitoshi; Shozu, Makio; Shimizu, Wataru; Yasukochi, Satoshi; et al.
Abstract: Objectives: To investigate the clinical course of fetal tachycardia and analyze the impact of intrauterine treatment on the postnatal treatment and patient outcomes. Study design: This was a retrospective review of cases of fetal tachycardia that occurred from 2004 to 2006. Data were collected from questionnaires that were sent to all 750 secondary or tertiary perinatal care centers in Japan. Results: Eighty-two cases (14 with fetal hydrops) were analyzed (supraventricular tachycardia [SVT], n  = 52; atrial flutter [AFL], n  = 23; and ventricular tachycardia, n  = 7). The overall mortality was 3.7%. Intrauterine treatment was performed for 41 fetuses (50.0%). Digoxin, flecainide and sotalol were mainly used for SVT and AFL. Fetal tachycardia resolved in 90.0% (27/30) of the cases without fetal hydrops and 90.9% (10/11) of the cases with fetal hydrops. Intrauterine treatment significantly reduced the incidence of cesarean delivery (29.3 vs. 70.7%, p  < .01), preterm birth (12.2 vs. 41.5%, p  = .02) and neonatal arrhythmias (48.8 vs. 78.0%, p  = .01) in comparison to untreated fetuses. Conclusions: This nationwide survey revealed that intrauterine treatment was performed for approximately half of the cases of fetal tachycardia and was associated with lower rates of cesarean delivery, premature birth and neonatal arrhythmias in comparison to untreated fetuses.